Propuesta metodológica transdiciplinaria “el riachuelo” para el aprendizaje de biología animal “invertebrados” con los estudiantes de cuarto semestre de la carrera de Pedagogía de las Ciencias Experimentales Química y Biología periodo octubre 2020 - marzo 2021 - Cisa Guzmán, Elsa Alicia (2021)
Transdisciplinarity is a fundamental methodology for learning Animal Biology. Transdisciplinarity is also an essential component for the academic training of students. However, in the Pedagogy of Experimental Sciences, Chemistry and Biology major, at the school of Education, Human Development and Technologies, the methodologies applied for learning Animal Biology is traditional. This traditional methodology uses excessive PowerPoint presentations and very little experimental practice or observation of natural contextualized environments. For this reason, this study suggests the application of the transdisciplinary method "El Riachuelo" for the learning of Animal Biology, specifically for "Invertebrates." We worked with 15 fourth-semester students. The research design was non-experimental, bibliographic, correlational, inductive-deductive, and. The survey technique was used for data collection, and the instrument was the questionnaire. Results suggest that the transdisciplinary methodology facilitates the learning of invertebrates and the acquisition of new knowledge by 80%. It is recommended to design a transdisciplinary methodological proposal using diverse natural learning scenarios and the support of multimedia resources to facilitate the experimental learning of Animal Biology.